Parental satisfaction and its associated factors with neonatal intensive care unit services at public hospitals in Bahir Dar, Northwest Ethiopia - Ayichew Alemu; Balew Zeleke; Friehiwot Girma Gessesse; Fentahun Meseret; Fenta Wondimeneh; Assefa Desalew (Elsevier, 2022)
Background: Parental satisfaction is an effective strategy to improve the quality of neonatal care and reduce neonatal mortality. Low parental satisfaction may result in discharge against medical advice, increased neonatal readmission, morbidity, and mortality. We found a scarcity of research on parental satisfaction and its factors associated with neonatal care unit services. This study aimed to assess parental satisfaction and its associated factors in public referral hospitals in Bahir Dar, Ethiopia. Methods: A facility-based cross-sectional study was conducted on 400 parent-neonate pairs. Participants were selected using a systematic random sampling technique. We used the Neonatal Satisfaction Survey (NSS-8) tool to collect data through face-to-face interviews. Data were entered using Epi data 3.1 and analyzed using the Statistical Package for the Social Sciences (SPSS) version 25. Multivariable logistic regression analysis was conducted using the adjusted odds ratio (aOR) with a 95% confidence interval (CI) to identify associated factors. Statistical significance was set at p < 0.05. Findings: A total of 400 parent-neonate pairs were included in this study. The mean and standard deviation of parental age was (29.4 ± 6.2) years. Overall parental satisfaction was 55.0% (95% CI:50.0-59.9%). Parental age (aOR = 2.03;95% CI:1.13-3.64), parental sex (aOR = 2.27; 95% CI:1.35-3.80), length of hospital stay (aOR = 5.09; 95% CI: 2.15-12.01), a history of readmission (aOR = 0.34; 95% CI:0.16-0.76), and involvement in decision making (aOR = 2.80; 95% CI:1.76-4.46) were associated with overall parental satisfaction. Conclusion: More than half of the participants were satisfied with the neonatal care provided to their infants. Parental age, sex, length of hospital stay, history of readmission, and involvement in decision-making were factors affecting parental satisfaction. We recommend paying more attention to parental involvement in decision-making for the care of their newborns, parents with a long duration of admission, and the need for continuity of care to improve parental satisfaction with neonatal care.